Comparison of the catching efficiency of the traditional and modified fish corral in Panguil Bay. - Acuña, Rodrigo E.
This study was conducted in two fishing sites of fish corral in Panguil Bay namely ; Malaubang, Ozamis City and Maquilao, Tangub City from November 21, 1994 to July 10, 1995. Two types of fish corral such as traditional and modified were identified. Results showed that average catch per trip was higher in the traditional fish corral (5.1 kg/day) compared to the modified fish corral (4.2 kg/day). The traditional fish corral also have a higher species richness (mean= 105 species) against the modified (mean=50 species). about 90% of the catch of the traditional fish corral are commercially important species is significantly higher than the other type (50%). Catches of the the traditional and modified fish corral largely consist of shrimps (Metapenaeus ensis; MFC; Penaeus indicus: TFC). Based on the relative density and weight of the total catch, Metapenaeus ensis (mean+222 individuals) is recorded as the most dominant species caught by the modified fish corral while Penaeus indicus (mean=38 individuals) exhibited as a dominant species in the traditional fish corral. Results of the statistical analyses on the data collected on irregular sampling dates show no significant difference on the catches between the traditional and modified. Significant difference is observed on the catches collected during the same sampling dates. Traditional fish corral is more efficient because it has higher catch per trip, species richness and high percentage of commercially important species. Modified fish corral as well, is effective with regards to tis catch quantity, however it is inefficient in terms of its catch quality, i.e., of low commercial value.